Exploration of Endophytic Bacteria from Katuk Plants (Sauropus androgynus L.) - Sri Ayu Anggita (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This study aimed to explore and identify endophytic bacteria from katuk plants (Sauropus androgynus L.) and evaluate their potential as biological control agents. A total of 14 bacterial isolates were successfully obtained from the roots, stems, and leaves of katuk plants. Safety assessments were conducted through hypersensitivity response (HR) and hemolysis (HL) tests. The HR test on tobacco plants indicated that all isolates were non-pathogenic, as no necrotic symptoms were observed. However, the hemolysis test revealed two isolates capable of forming α-hemolysis zones on blood agar, suggesting potential risks to mammals. Antibacterial activity against the plant pathogen Ralstonia solanacearum was evaluated using spot inoculation methods. The results showed that none of the isolates were able to inhibit the growth of R. solanacearum. Although the isolates may produce antibacterial compounds, the amounts are likely insufficient or involve unidentified active compounds. Further studies are needed to fully characterize these isolates and explore their potential applications in sustainable agriculture.